The Effect of Tax Morale on the Compliance of State Civil Apparatus Taxpayers at PTNBH with the Role of a Supportive Corporate Environment as a Moderating Variable - Herry Laksito (Jurnal Akuntansi dan Perpajakan, 2022)
The purpose of this study is to examine the effect of tax morale on taxpayer compliance in PTNBH. In addition, this study also aims to examine the effect given by a supportive corporate environment as a moderating variable. The data used is primary data obtained from state civil servants who work in higher education institutions with legal entities (PTNBH). Testing using Moderated Regression Analysis with SPSS tools. The results of the study show that tax morale has a significant effect on taxpayer compliance. A supportive corporate environment is also proven to be able to strengthen the relationship that is formed between the independent variables and the dependent variable in this study.